Prevalence of metabolic dysfunction‐associated steatotic liver disease in people living with HIV and on antiretroviral treatment: A systematic review and meta‐analysis protocol - Amogelang Sedibe; Khanyisa Maswanganyi; Nomusa C. Mzimela; Mlindeli Gamede (Health Science Reports)
Abstract Introduction Metabolic dysfunction‐associated steatotic liver disease (MASLD) has become the most common hepatic condition globally. The prevalence of MASLD continues to increase, paralleling the consistent rising rates of risk factors such as obesity and type 2 diabetes. Literature suggests that human immunodeficiency virus‐infected (HIV‐infected) individuals may have an increased risk of developing MASLD due to a complex interplay of factors including antiretroviral therapy. Since the development and widespread use of effective antiretroviral therapy (ART), HIV‐induced liver disease has continued to be the predominant cause of liver‐related morbidity and mortality. This protocol serves to narrate the methods that will be employed in conducting the published literature search for the systematic review and meta‐analysis which will report on the global prevalence of MASLD on people living with HIV and on ARV treatment. Methods The search of literature will be done using search engines or electronic databases including PubMed, Google Scholar, African Journal Online, and ResearchGate. Specific keywords will be used to search literature that has reported on the prevalence of MASLD among HIV patients receiving antiretroviral treatment, this will ensure the reproducibility of the study. Cross‐sectional and longitudinal observational studies, retrospective cohort studies, clinical trial studies, meta‐analyses, and systematic reviews that were published in the English language from 1990 to 2024 will be included. Animal studies will be excluded. Three independent reviewers will conduct the selection process and select studies that meet the eligibility criteria. A quality assessment tool, Downs and Blacks will be used to assess the risk of bias of the selected studies. A review manager will be used for meta‐analysis of collected data and the Grading of Recommendations Assessment, Development, and Evaluation tool will assess the strength of evidence. Ethics, dissemination, and registration The review will not require ethical clearance as it will only include data that is publicly available in published reports. The results of this review will be disseminated through publications. This study is registered with PROSPERO (CRD42024516814).